Percepción de la enseñanza de las matemáticas en la Licenciatura de Administración - Góngora Villeda, Sonia (Universidad Autónoma Metropolitana, 2024)
In this research describes the perception that students have about the teaching of mathematics in the Bachelor of Administration at the Universidad Autónoma Metropolitana Unidad Iztapalapa; A quantitative investigation is carried out to identify which mathematical knowledge students have greater difficulty/easiness in, what their experience has been with the mathematical contents they have studied and to know if they recognize the importance of studying mathematics as well as its application in the professional field, taking as reference the corresponding data from the last 5 years on the approval, failure and resignation rates of Teaching and Learning Units with high mathematical content. It is concluded that the students have a satisfactory perception about the teaching of mathematics in the degree and although they recognize the importance for the application in the work field, they believe that it could be improved by including more mathematical topics that can help them put into practice the knowledge obtained. Key Words: Mathematics, Administration, Teaching-learning process.; En esta investigación, se hace una descripción de la percepción que tienen los estudiantes sobre la enseñanza de las matemáticas en la Licenciatura de Administración en la Universidad Autónoma Metropolitana Unidad Iztapalapa; se realiza una investigación cuantitativa para identificar cuáles son los conocimientos matemáticos en los que los estudiantes tienen mayor dificultad/facilidad, cuál ha sido su experiencia con los contenidos matemáticos que han estudiado y para saber si es que reconocen la importancia del estudio de las matemáticas así como su aplicación en el campo profesional, teniendo como referencia los datos correspondientes de los últimos 5 años sobre los índices de aprobación, reprobación y renuncias de las Unidades de Enseñanza y Aprendizaje (UEA) con alto contenido matemático. Se concluye con que los estudiantes tienen una satisfactoria percepción sobre la enseñanza de las matemáticas en la licenciatura y aunque reconocen la importancia para la aplicación en el campo laboral, creen que se podría mejorar en la inclusión de más temas matemáticos que puedan ayudarlos a poner en práctica los conocimientos obtenidos. Palabras clave: Matemáticas, Administración, Proceso de enseñanza – aprendizaje